Ionic liquid-covalent organic framework carbon capture material with positive local electric field and preparation method of ionic liquid-covalent organic framework carbon capture material

Through the preparation technology of the host-guest interaction of ionic liquid-covalent organic frame composites, the problem of insufficient selectivity of mixed matrix membranes in gas separation such as CO2/CH4 is solved, and carbon capture materials with high selectivity and permeability are achieved .

CN119455702APending Publication Date: 2025-02-18SHIHEZI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411846935.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing mixed matrix membranes have insufficient selectivity in the separation of gases such as CO2/CH4, and are limited by pore size, making it difficult to meet the needs of industrial applications.

Method used

A ionic liquid-covalent organic framework composite was developed to prepare through host-guest interaction to form a spherical structure, which was used to prepare a mixed matrix membrane and use a positive local electric field to increase the selectivity of CO2.

Benefits of technology

It achieves high selectivity and permeability of gas separation such as CO2/CH4, overcomes the pore size limitations of traditional membrane separation methods, and meets the needs of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005189471400000011
    Figure HDA0005189471400000011
  • Figure HDA0005189471400000012
    Figure HDA0005189471400000012
  • Figure HDA0005189471400000013
    Figure HDA0005189471400000013
Patent Text Reader

Abstract

The invention provides an ionic liquid-covalent organic framework with a positive local electric field as well as a preparation method and application of the ionic liquid-covalent organic framework in carbon capture, and belongs to the technical fields of composite material preparation, carbon capture and mixed matrix membrane preparation. The ionic liquid-covalent organic framework composite material is prepared on the basis of host-guest interaction between ionic liquid and a covalent organic framework; in the composite material, bromide ions in the imidazolyl ionic liquid are more likely to be combined with methoxyl groups in the covalent organic framework through non-covalent interaction, so that the ionic liquid is confined in pore channels of the covalent organic framework; the ionic liquid-covalent organic framework composite material can be used as a filler to prepare a mixed matrix membrane, the preparation process of the mixed matrix membrane is simple, the reaction is controllable, the raw materials are cheap and easy to obtain, the conditions are mild, and the ionic liquid-covalent organic framework composite material has good application in carbon capture, especially separation of CO2 / CH4, CO2 / N2 and CO2 / H2 mixed gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite material preparation, carbon capture and mixed matrix membrane preparation, and specifically relates to an ionic liquid-covalent organic framework composite material with a positive local electric field, a preparation method thereof and an application in carbon capture. Background Art

[0002] The increase in CO2 concentration in the atmosphere will lead to serious consequences such as global warming and ecological damage, so measures need to be taken to limit CO2 emissions. However, CO2 emissions are unavoidable during production operations, and CO2 is a rich C1 resource with broad application prospects in the chemical, food, agriculture, oil and gas extraction and other industries. Therefore, separating and capturing CO2 can not only effectively cope with the greenhouse effect, but also make full use of resources, realize resource recycling, help improve social and economic benefits, and have broad development prospects.

[0003] The choice of CO2 separation process depends on many factors, including purity, recovery rate and cost. Among them, membrane separation is considered to be one of the most promising CO2 separation technologies due to its advantages of high efficiency, low energy consumption and low cost. Mixed matrix membranes (MMMs) are blended by dispersed fillers and continuous polymer matrices. The choice of fillers determines the upper limit of membrane performance. Common fillers are limited by pore size, and the separation performance is usually far below the requirements of industrial applications. Therefore, a completely different CO2 screening method is needed to solve the problem caused by non-selective pores in MMMs. Since the opposite surface electrostatic potentials of CO2 and CH4 provide feasibility for the realization of this idea, the presence of charge can form an electric field in the local space, and the use of electric field for CO2 / CH4 screening can effectively avoid the limitation of pore size. Ionic liquids have asymmetric cations and anions and can be used as effective guest materials for regulating the charge of porous materials. The charged ionic liquid-covalent organic framework induces a local electric field in MMMs. Due to the "screening effect" of the positive local electric field on CO2 and CH4, the electrostatic interaction between the negatively charged O atoms in CO2 and the positive local electric field is stronger than that between the positively charged H atoms in CH4, thereby improving the selectivity of MMMs. Therefore, it is necessary to develop a new ionic liquid-covalent organic framework composite material and use it as a filler to prepare carbon capture materials. Summary of the invention

[0004] In view of some deficiencies in the prior art, the present invention provides an ionic liquid-covalent organic framework composite material, a preparation method thereof and an application in carbon capture; the present invention prepares an ionic liquid-covalent organic framework composite material based on the host-guest interaction between the ionic liquid and the covalent organic framework; in the composite material, the bromide ions in the imidazole-based ionic liquid are more inclined to combine with the methoxy groups in the covalent organic framework through non-covalent interactions, thereby confining the ionic liquid in the pores of the covalent organic framework; the ionic liquid-covalent organic framework composite material can be used as a filler to prepare a mixed matrix membrane, the preparation process of the mixed matrix membrane is simple, the reaction is controllable, the raw materials are cheap and easily available, and the conditions are mild, and it has good application in carbon capture, especially in the separation of CO2 / CH4, CO2 / N2 and CO2 / H2 mixed gases.

[0005] In order to achieve the above technical effects, the present invention adopts the following technical means:

[0006] The present invention first provides an ionic liquid-covalent organic framework composite material, wherein the ionic liquid-covalent organic framework composite material is obtained by compounding ILs2C and TPB-DMTP-COF, wherein the ILs2C is confined in the pores of TPB-DMTP-COF; and the ionic liquid-covalent organic framework composite material has a spherical structure.

[0007] The present invention also provides a method for preparing the above-mentioned ionic liquid-covalent organic framework composite material, comprising the following steps:

[0008] (1) 1-vinylimidazole and 2-bromoethylamine hydrobromide are added to anhydrous ethanol to obtain a mixture A, and then the mixture A is uniformly dispersed. The mixture A is heated and stirred under reflux in a N2 atmosphere. After the reaction is completed, the solution is cooled to room temperature to form a viscous solid B. The solid B is then washed with anhydrous ethanol and dried overnight to obtain an ionic liquid ILs2C.

[0009] (2) Add 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxybenzene-1,4-dicarboxaldehyde to acetonitrile to obtain a mixture C, and then uniformly disperse the mixture C. Then, add an acetic acid solution to the mixture C and uniformly disperse it. Finally, the mixture C is allowed to react under static conditions to precipitate a precipitate D. The precipitate D obtained by centrifugation is washed with acetonitrile, water and ethanol. The precipitate D is dried at 80°C overnight to obtain a covalent organic framework TPB-DMTP-COF.

[0010] (3) ILs2C was added to methanol and stirred for 30 minutes, and then TPB-DMTP-COF was added under stirring to obtain a mixture E. The mixture E was ultrasonically dispersed and then washed with methanol. Finally, the mixture E was dried overnight to obtain an ionic liquid-covalent organic framework composite material.

[0011] Preferably, in step (1), the amount of 1-vinylimidazole, 2-bromoethylamine hydrobromide, and anhydrous ethanol is in the following relationship: 20-60 mmol: 20-60 mmol: 10-50 mL;

[0012] The heating reaction conditions are 50-110° C. for 10-48 hours;

[0013] The drying condition is drying at 30-150° C. for 5-48 hours.

[0014] Preferably, in step (2), the usage ratio of 1,3,5-tris(4-aminophenyl)benzene, 2,5-dimethoxybenzene-1,4-dicarbaldehyde and acetic acid is 0.01-0.03 mmol: 0.03-0.21 mmol: 2-20 mL;

[0015] The acetic acid concentration is 1 to 10 mol / L;

[0016] The static reaction condition is to react at 0-80° C. for 24-96 hours.

[0017] Preferably, in step (3), the usage ratio of ILs2C, TPB-DMTP-COF, and methanol is 0.05-1 g: 0.05-1 g: 5-30 g;

[0018] The ultrasonic dispersion time is 0.5 to 3 hours.

[0019] The present invention also provides the use of the ionic liquid-covalent organic framework composite material in the preparation of carbon capture materials.

[0020] Preferably, the carbon capture material comprises a mixed matrix membrane and the carbon capture comprises separation of a CO2 / CH4 mixed gas.

[0021] The present invention also provides a carbon capture material, which uses the above-mentioned ionic liquid-covalent organic framework composite material as a filler and polyether polyimide block Pebax as a polymer matrix; the carbon capture material is formed by physically blending the filler and the polymer matrix at room temperature; the thickness of the carbon capture material is 100-130μm; the mass percentage of the filler in the carbon capture material is 1% to 14%.

[0022] The present invention also provides a method for preparing the above carbon capture material, which specifically comprises the following steps:

[0023] (1) dissolving a polyether polyimide block Pebax in a mixed solution of ethanol and water to obtain a polyether polyimide block Pebax solution;

[0024] (2) physically blending the ionic liquid-covalent organic framework material and the polyether polyimide block Pebax solution, and stirring at room temperature to obtain a casting solution;

[0025] (3) Casting and drying the casting solution to obtain the carbon capture material.

[0026] Preferably, in the carbon capture material, the ionic liquid-covalent organic framework material accounts for 1% to 14% of the mass percentage of the carbon capture material.

[0027] The present invention also provides application of the above carbon capture material in carbon capture.

[0028] Preferably, the applications include separation of CO2 / CH4, CO2 / N2 and CO2 / H2 mixed gases.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The present invention provides a novel ionic liquid-covalent organic framework composite material. Different from the prior art, the ionic liquid-covalent organic framework material of the present invention is prepared by a host-guest interaction method, which can effectively avoid the harsh conditions of covalent grafting.

[0031] (2) The present invention uses the prepared ionic liquid-covalent organic framework material as a filler and physically blends it with the polyether-polyimide block copolymer Pebax to form a mixed matrix membrane with a unique positive local electric field. The mixed matrix membrane can have a positive local electric field, thereby improving the selectivity of CO2 through the sieving effect. Therefore, the ionic liquid-covalent organic framework composite material of the present invention effectively improves the selectivity and separation performance of CO2 / CH4 in the membrane.

[0032] (3) The mixed matrix membrane with polyether-polyamide block copolymer (Pebax) as the matrix of the present invention constructs an efficient CO2 transfer path in the membrane, improves the permeability-selectivity performance of the mixed matrix membrane, overcomes the trade-off effect, and has high permeability and high separation factor. The preparation process of the mixed matrix membrane is simple, the reaction is controllable, the raw materials are cheap and easy to obtain, and the conditions are mild, which can promote the complementary advantages of the filler and the polymer matrix. The research results show that the permeability selectivity of the mixed matrix membrane of the present invention for CO2 / CH4 mixed gas has a maximum CO2 flux of 654.8±19.7barrer and a CO2 / CH4 selectivity of 36.5±0.4, which has a good application in carbon capture, especially in the separation of CO2 / CH4 mixed gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a transmission electron microscopy image of the ionic liquid-covalent organic framework.

[0034] Figure 2 It is the PXRD pattern of ionic liquid-covalent organic framework.

[0035] Figure 3 This is the Zeta potential diagram of ionic liquid-covalent organic framework.

[0036] Figure 4 This is a scanning electron microscope cross-sectional image of the Pebax / ionic liquid-covalent organic framework mixed matrix membrane.

[0037] Figure 5 is a scanning electron microscope cross-sectional image of the prepared pure Pebax film.

[0038] Figure 6 Surface Zeta potential diagram of mixed matrix membrane containing ionic liquid-covalent organic framework composite and pure Pebax membrane. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto. Experimental methods without specific conditions in the embodiments are all based on conventional conditions; the reagents and materials used, unless otherwise specified, can be obtained from commercial sources.

[0040] Example 1: Preparation of ionic liquid-covalent organic framework composite materials

[0041] (1) 3.62 ml of 1-vinylimidazole and 8.2 g of 2-bromoethylamine hydrobromide were added to 30 ml of anhydrous ethanol to obtain a mixture A, which was then uniformly dispersed. The mixture A was heated at 80° C. under a N2 atmosphere and stirred under reflux for 24 h. After the reaction was completed, the solution was cooled to room temperature to form a viscous solid B. The solid B was then washed with anhydrous ethanol and dried overnight to obtain an ionic liquid ILs2C.

[0042] (2) Add 14.1 ml of 1,3,5-tris(4-aminophenyl)benzene and 11.7 ml of 2,5-dimethoxybenzene-1,4-dicarboxaldehyde to 5 ml of acetonitrile to obtain a mixture C, and then uniformly disperse the mixture C. Then, add 0.3 ml of a 12 mol / L acetic acid solution to the mixture C and uniformly disperse it. Finally, the mixture C is allowed to react for 72 hours under static conditions, and a precipitate D is precipitated. The precipitate D obtained by centrifugation is washed with acetonitrile, water and ethanol. The precipitate D is dried overnight to obtain a covalent organic framework TPB-DMTP-COF.

[0043] (3) 0.3 g of ILs2C was added to 15 g of methanol and stirred for 30 minutes, and then 0.1 g of TPB-DMTP-COF was added under stirring to obtain a mixture E. The mixture E was ultrasonically dispersed for 1 h and then washed with methanol. Finally, the mixture E was dried overnight to obtain an ionic liquid-covalent organic framework composite material.

[0044] Figure 1 This is a transmission electron microscope image of an ionic liquid-covalent organic framework. Figure 1 It can be seen that the ionic liquid-covalent organic framework presents a spherical morphology; the host-guest interaction between the bromide ions of the ionic liquid ILs2C and the covalent organic framework TPB-DMTP-COF enables the ionic liquid and the covalent organic framework to be successfully composited.

[0045] Figure 2 This is the PXRD diagram of the ionic liquid-covalent organic framework. It can be seen from the figure that the diffraction peak of the ionic liquid-covalent organic framework is well preserved, which shows that the loading of the ionic liquid does not affect the crystal structure of the covalent organic framework.

[0046] Figure 3 This is the Zeta potential diagram of the ionic liquid-covalent organic framework. It can be seen from the figure that the overall charge of the covalent organic framework is changed from negative to positive through the loading of the ionic liquid, which provides a key condition for the ionic liquid-covalent organic framework to construct a positive local electric field in MMMs.

[0047] Example 2: Preparation of carbon capture materials containing ionic liquid-covalent organic framework composite materials

[0048] Weigh 0.645g 1657 was dissolved in 10 mL of a mixed solution of ethanol and water in a mass fraction ratio of 7:3, and heated and stirred in a water bath at 80° C. for 2 h to dissolve all the Pebax particles, thereby preparing a Pebax matrix solution with a mass fraction of 6 wt %, which was set aside.

[0049] 0.0199 g of the ionic liquid-covalent organic framework prepared in Example 1 was physically blended with 6 wt% Pebax matrix solution, and the mixture was stirred at room temperature for 4 h to obtain a casting solution, and the casting solution was poured onto a clean culture dish for casting; the mixture was dried at room temperature (25°C) for 48 h, and then vacuum dried in a vacuum drying oven at 40°C to remove the residual solvent on the surface of the mixed matrix membrane, thereby obtaining the carbon capture material containing the ionic liquid-covalent organic framework composite material, i.e., the Pebax / ionic liquid-covalent organic framework mixed matrix membrane.

[0050] It was measured that the thickness of the Pebax / ionic liquid-covalent organic framework mixed matrix membrane was 106 μm. Figure 4This is a scanning electron microscope cross-section of the Pebax / ionic liquid-covalent organic framework mixed matrix membrane. Figure 4 It can be seen that after the ionic liquid-covalent organic framework is introduced into the Pebax matrix, the cross-section of the mixed matrix membrane becomes rough, which proves the introduction of the filler, and the ionic liquid-covalent organic framework is evenly distributed in the mixed matrix membrane without agglomeration.

[0051] This example also performs a performance test on the prepared Pebax / ionic liquid-covalent organic framework mixed matrix membrane, and the test steps are as follows:

[0052] (1) The prepared Pebax / ionic liquid-covalent organic framework mixed matrix membrane was used for CO2 / CH4 mixed gas separation test;

[0053] (2) using a mixed gas of 80 vol% CH4 and 20 vol% CO2 as the raw gas, and then wetting the dried Pebax / ionic liquid-covalent organic framework mixed matrix membrane with deionized water so that the volume of the Pebax / ionic liquid-covalent organic framework mixed matrix membrane after wetting is approximately twice the original volume, and placing it in a membrane pool for permeability testing;

[0054] (3) A round stainless steel tank was placed in the oven to study the Pebax / ionic liquid-covalent organic framework mixed matrix membrane (12.56 cm 2 , center part) separation performance;

[0055] (4) Testing the gas permeability of MMMs under different loads:

[0056] The feed gas was introduced upstream of the membrane, the flow rate was controlled at 50 mL / min, and the pressure range was 0.2-0.8 MPa. The permeability of CO2 and CH4 was calculated based on the sweep gas flow rate and its composition. The effects of H2 back diffusion and concentration polarization on data analysis can be ignored because the volume of the feed gas is much larger than the sweep gas (H2), and the back diffusion of H2 cannot change the composition of the feed gas. Therefore, H2 is suitable as the sweep gas on the downstream side of the membrane, and the flow rate is controlled at 30 mL / min. The content of each component in the permeate phase gas was determined by gas chromatograph (GC 2014C).

[0057] The test results show that the CO2 flux is 654.8 Barrer (1 Barrer = 10 -10 cm 3 cm / cm 2 s cmHg), CO2 / CH4 selectivity is 36.5.

[0058] Comparative Example 1:

[0059] For comparison, 0.645 g of Pebax particles were weighed and dissolved in a mixed solution of 70% ethanol / 30% water by mass. After stirring at 80°C for 2 hours, the resulting casting liquid was poured onto a clean ultra-flat surface dish and cast. It was dried at room temperature (25°C) for 48 hours and then placed in a vacuum oven at 40°C for 24 hours to remove the residual solvent, thereby obtaining a Pebax film with a thickness of 102 μm.

[0060] Figure 5 is a scanning electron microscope cross-sectional image of the prepared pure Pebax film. Figure 5 It can be seen that the cross section of the pure Pebax membrane shows the typical morphology of a smooth, dense and defect-free polymer membrane. At 25°C and 2 bar, the Pebax membrane was used for the separation test of a CO2 / CH4 mixed gas (the volume ratio of CO2 to CH4 was 2:8) with a CO2 volume fraction of 20%. The CO2 flux was tested to be 280 barrer and the CO2 / CH4 selectivity was 25.

[0061] Figure 6 The surface zeta potential diagram of mixed matrix membranes containing ionic liquid-covalent organic framework composites and pure Pebax membranes. Figure 6 It can be seen that the negative potential of the mixed matrix membrane containing ionic liquid-covalent organic framework is lower than that of the pure Pebax membrane, indicating that there is a positive local electric field inside.

[0062] In summary, the present invention prepares an ionic liquid-covalent organic framework composite material based on the host-guest interaction between the ionic liquid and the covalent organic framework; in the composite material, the bromide ions in the imidazole-based ionic liquid are more inclined to combine with the methoxy groups in the covalent organic framework through non-covalent interactions, thereby achieving the confinement of the ionic liquid in the pores of the covalent organic framework; the ionic liquid-covalent organic framework composite material can be used as a filler to prepare a mixed matrix membrane, and the preparation process of the mixed matrix membrane is simple, the reaction is controllable, the raw materials are cheap and easy to obtain, and the conditions are mild, and it has great application in carbon capture, especially in the separation of CO2 / CH4, CO2 / N2 and CO2 / H2 mixed gases.

[0063] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.

Claims

1. A method for preparing an ionic liquid-covalent organic framework composite material, characterized in that: The steps include: (1) 1-vinylimidazole and 2-bromoethylamine hydrobromide are added to anhydrous ethanol to obtain a mixture A, and then the mixture A is uniformly dispersed. The mixture A is heated and stirred under reflux in a N2 atmosphere. After the reaction is completed, the solution is cooled to room temperature to form a viscous solid B. The solid B is then washed with anhydrous ethanol and dried overnight to obtain an ionic liquid ILs2C. (2) Add 1,3,5-tris(4-aminophenyl)benzene and 2,5-dimethoxybenzene-1,4-dicarboxaldehyde to acetonitrile to obtain a mixture C, and then uniformly disperse the mixture C. Then, add an acetic acid solution to the mixture C and uniformly disperse it. Finally, the mixture C is allowed to react under static conditions to precipitate a precipitate D. The precipitate D obtained by centrifugation is washed with acetonitrile, water and ethanol. The precipitate D is dried overnight to obtain a covalent organic framework TPB-DMTP-COF. (3) ILs2C was added to methanol and stirred for 30 minutes, and then TPB-DMTP-COF was added under stirring to obtain a mixture E. The mixture E was ultrasonically dispersed and then washed with methanol. Finally, the mixture E was dried overnight to obtain an ionic liquid-covalent organic framework composite material.

2. The method for preparing the ionic liquid-covalent organic framework composite material according to claim 1, characterized in that: In step (1), the amount of 1-vinylimidazole, 2-bromoethylamine hydrobromide, and anhydrous ethanol is in the following relationship: 20-60 mmol: 20-60 mmol: 10-50 mL; The heating reaction conditions are 50-110° C. for 10-48 hours; The drying condition is drying at 30-150° C. for 5-48 hours.

3. The method for preparing the ionic liquid-covalent organic framework composite material according to claim 1, characterized in that: In step (2), the usage ratio of 1,3,5-tris(4-aminophenyl)benzene, 2,5-dimethoxybenzene-1,4-dicarbaldehyde and acetic acid is 0.01-0.03 mmol: 0.03-0.21 mmol: 2-20 mL; The acetic acid concentration is 1 to 10 mol / L; The static reaction condition is to react at 0-80° C. for 24-96 hours.

4. The method for preparing the ionic liquid-covalent organic framework composite material according to claim 1, characterized in that: In step (3), the usage ratio of ILs2C, TPB-DMTP-COF and methanol is 0.05-1 g: 0.05-1 g: 5-30 g; The ultrasonic dispersion time is 0.5 to 3 hours.

5. The ionic liquid-covalent organic framework composite material prepared according to the method of any one of claims 1 to 4, characterized in that: The ionic liquid-covalent organic framework composite material is obtained by compounding ILs2C and TPB-DMTP-COF, wherein the ILs2C is confined in the pores of TPB-DMTP-COF; and the ionic liquid-covalent organic framework composite material has a spherical structure.

6. Use of the ionic liquid-covalent organic framework composite material according to claim 5 in the preparation of carbon capture materials.

7. The use according to claim 6, characterized in that: The carbon capture material includes a mixed matrix membrane, and the carbon capture includes separation of CO2 / CH4, CO2 / N2 and CO2 / H2 mixed gases.

8. A carbon capture material, characterized in that: The carbon capture material uses the ionic liquid-covalent organic framework composite material described in claim 5 as a filler and the polyether polyimide block Pebax as a polymer matrix; the carbon capture material is formed by physically blending the filler and the polymer matrix at room temperature; the thickness of the carbon capture material is 100-130 μm; the mass percentage of the filler in the carbon capture material is 1% to 14%.

9. Use of the mixed matrix membrane according to claim 8 in CO2 capture.